The correlation between media and technology: The context of the gradual rise of new media - Kohutova, Radka (Bodhi: An Interdisciplinary Journal, 2012)
DOI: http://dx.doi.org/10.3126/bodhi.v4i1.5810 Bodhi 2010 4(1): 48-70